Immunology of recurrent vaginitis - Witkin, S S (American journal of reproductive immunology and microbiology : AJRIM, 1987)
Recent evidence suggests that recurrent vaginitis can arise as a consequence of a transient and localized inhibition of cell-mediated immunity. Lymphocytes from many women with this disorder manifest a reduced in vitro proliferative response to Candida albicans. The inhibition appears to be due to increased production by the patients' macrophages of prostaglandin E2, which inhibits interleukin-2 production and thereby blocks lymphocyte proliferation. When lymphocyte responses are impaired, C. albicans can readily proliferate and initiate a clinical infection. Prostaglandin E2 production can arise as a consequence of a vaginal allergic response. IgE antibodies to C. albicans, ryegrass, contraceptive spermicides, and seminal plasma have been detected in vaginal fluids from recurrent vaginitis patients. The role of male factors in inducing immune alterations and vaginitis in the female partner has been underestimated. Medications or chemicals ingested by the male and present in his semen may be transmitted to sensitized females by coitus. In addition, male-specific allergic responses may be induced in females through the seminal transfer of specific IgE antibodies. Future efforts both to eliminate clinical vaginal infections and to reduce susceptibility of the host to vaginal immunosuppression should improve the efficacy of treatment for this disorder